A comparison of the physiological and technical effects of high-intensity running and small-sided games in young soccer players - Radziminski, L.; Rompa, P.; Barnat, W.; Dargiewicz, R.; Jastrzebski, Z. (International Journal of Sports Science and Coaching, 2013)
The aim of this study was to investigate the effects of high-intensity interval running and small-sided game training programs on the physical capacity and the level of soccer-specific technical skills in young soccer players. Twenty male soccer players (U-16) were divided into two groups (running group - RG, small-sided game group - SSGG) and completed two different 8-week training programs. The intervention consisted of two training sessions a week (RG - 5x4 min running, with an active recovery period of 3 min; SSGG -3vs.3 games or 3vs.3 with a neutral player for 5x4 min, with an active recovery period of 3 min). A significant group x time interaction was found in the VO2max (p = 0.025). Moreover, the significant pre to post changes of VO2max were observed in the SSGG (p = 0.032). The differences between the results of shuttle runs and sprint tests were not significant with the exception of 5 m sprint in RG (p = 0.04). An improvement in the peak power and total work capacity was observed in the RG and SSGG. A significant improvement (p = 0.014) in soccer-specific technical skills level was noted only in the SSGG. The results of this study suggest that the small-sided games, compared with interval running, are more highly recommended training drills for the coincident development of physical capacity and technical skills in young soccer players.